Auto-compatibilidad genética y calidad física de almendra en veinte híbridos interclonales de cacao (Theobroma cacao l.) - Véliz Apolo, Bryan Manuel (2015)
The present research was carried out on the Experimental Farm "The dam", which was used a completely randomized design, as treatments deemed 20 hybrids more a commercial witness JHVH-10, with three replicates, each experimental unit will be made up of five flowers, and to determine differences among treatment means the test of Tukey (P≤0. 05), be used in order to determine the Auto-compatibilidad the morphology of the flower and the physical quality post harvest of almonds of these new materials, for the variable of percentage of pollination excelled the T5 with the 60's flowers fertilized, matching the percentage of clone father LR14. Flower morphology variables stood out the T15 and T14 registering a larger 1.95 and 1.92 cm respectively, feel this directly related with the other variables already larger greater flower will be the weight, length and width of the petal and sepal and long-stalked; among the variables of physical quality of almond was found that the T5 log the IM highest 1.41 g, T3 obtained the lower NA 100g 67 units, the t stood out the T10 with a 7.97, the IM T1 present fewer ears with 18.81 units, in the the the T9 achievement 2.47 cm in size and for AA T1 record 1.32 cm wide; while cutting the T15 test entered in the category of commercial A.S.S.P.S. rating which is the highest with a 91 total of fermentation.